2015
DOI: 10.1159/000433581
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Possible Neuropathology and Clinical Relationships in 46 Sporadic Amyotrophic Lateral Sclerosis Patient Autopsies

Abstract: Background: Recent studies have suggested overlapping pathological features among motor neuron, cognitive and neurodegenerative diseases. Aims/Methods: Secondary analysis of 46 amyotrophic lateral sclerosis (ALS) patient autopsies was performed to independently assess pathological feature prevalence (e.g. percent of patients with any positive finding), degree of severity (e.g. mild, moderate, severe), and 2,200+ potential clinical/neuropathological correlations. The possible impact of gender, onset age, onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 62 publications
4
34
0
1
Order By: Relevance
“…There are many studies in the literature suggesting that neurodegenerative diseases share molecular characteristics; however, few studies have addressed this hypothesis with regard to AD and ALS (8, 19, 20). Findings from different studies point to certain common mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the literature suggesting that neurodegenerative diseases share molecular characteristics; however, few studies have addressed this hypothesis with regard to AD and ALS (8, 19, 20). Findings from different studies point to certain common mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, pathological changes of AD, especially neuritic plaques, were associated with older age and shorter survival time (20). In another study, Coan and Mitchell (20) analyzed 46 autopsies of patients with ALS and found that 22% of the cases met criteria for AD and 26% for FTD, 78% displayed neurofibrillary tangles, and 35% showed moderate increases in Aβ expression, especially in the amygdala, hippocampus, and the entorhinal and insular cortices. Likewise, ALS onset in patients who met the criteria for AD was more frequently bulbar; onset type had no impact on survival time.…”
Section: Introductionmentioning
confidence: 87%
“…Interestingly, brain Aβ may be increased in numerous neurologic conditions other than AD: traumatic brain injury, chronic traumatic encephalopathy, general anesthesia, amyotrophic lateral sclerosis, major depressive disorder, cerebral ischemia, and multiple sclerosis . Patients undergoing cardiac surgery or suffering cardiac arrest also show rapid changes in Aβ levels in CSF/plasma, even infants and children, probably from a combination of mechanical trauma and anesthetic insult.…”
Section: Physiological Role Of Aβmentioning
confidence: 99%
“…Although tau inclusions are rare in amyotrophic lateral sclerosis (ALS), 17 a favourable vascular risk profile is also observed. [18][19][20] ALS is associated with FTLD in 15% of cases.…”
Section: Discussionmentioning
confidence: 99%